The chemopreventive and anticancer potential against colorectal cancer of polyphenol-rich fruit extracts. Issue 4 (19th May 2018) - Majewska, Małgorzata; Lewandowska, Urszula
ABSTRACT: The consumption of vegetables and fruits, particularly apples, pomegranates, grapes, and berries, is associated with a decreased risk of developing cancer, especially colorectal cancer (CRC). This may be attributable to the presence of phytochemical constituents, such as polyphenols. This review summarizes the current state of knowledge concerning the chemopreventive and anti-CRC potential of polyphenol-rich apple, pomegranate, grape, and berry extracts with a focus on in vitro, in vivo, and clinical evidence. The extracts demonstrate antiproliferative, proapoptotic, antiangiogenic, antiinvasive, and antimetastatic activities toward colon cancer cell lines and in animal models and markedly influence preneoplastic lesions and malignancies in humans.